Anthropometric profiles of elite Asian female handball players - Hasan, A. A.; Reilly, T.; Cable, N. T.; Ramadan, J. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Handball has increased in status as a sport since its introduction in 1972 into the Summer Olympic Games. Whereas anthropometric profiles of female athletes have been reported for certain sports, data for elite handball players are limited. The current study was based on anthropometric measurements of 60 female Asian handball players competing in the continental championship, the aim being to identify any differences between countries and between playing positions. Methods: The setting was the 12th Asian Games in Hiroshima, Japan. Anthropometric data were obtained from 60 players including teams from China, Japan, Kazakhstan and South Korea. Measurements included height, mass, skinfold thicknesses: from these measures percent body fat and muscle mass were estimated. Profiles were compared between 4 nations and 4 positional roles by means of ANOVA. Results: Overall, mean (SD) values were 1.708 (0.068) m, 64.6 (7.7) kg, 20.8% (4.4%), 39.6% (5.2%) for stature, mass, percent body fat and percent muscle mass, respectively. There were small differences between players from different countries but no significant (P>0.05) influence of playing position. Players from Japan were shortest, lightest and lowest in adiposity. The Chinese players were tallest and had the greatest muscle mass. Conclusion: These female international handball players differed in some respects in anthropometric characteristics according to their country of origin. The Asian players were found to be relatively homogeneous across the different positions.